Penegakan Hukum Terhadap Kasus Pedophilia Ditinjau Dari KUHP Dan Qanun Jinayat - Wardana, Muhammad Noor; Jauhari, Imam; Isnaini, Isnaini (ARBITER: Jurnal Ilmiah Magister Hukum, 2021)
Bases to this study, take then three points of questionable such as; 1) what factors cause taking place pedophilia, 2) how to apply law enforcement to a pedophilia  case on Aceh, 3) what actions to be taken by Syariah Court to minimize pedophilia  criminal case. This study is an analysis descriptive research method with data research approach, to analyze the data of regulations rules regarding pedophilia cases. In collecting the data, adopted library research and field research. Still, in analyzing the data from variously resources, to classify them according to the purpose and aim of conducting the research. All the data that has been gained and classified should be interpreted later. The result indicated that 1) causes of occurrence any pedophilia cases mostly on the effect of environmental such as seeing video with porno, internal factor originally from the actor since he got abnormal sexual desires, external factor there is connecting with social and cultural aspects and due to advancement of technology and informatics. Still, locally, 2) Law enforcement with Qanun Jinayat is ruled in a Qanun Jinayat in Article 46 and 47 to this case one as actor should be sentenced with whips in 90 times  and set fine with 900 gram or jailed for 90 months. 3) in order to minimize pedophilia acts as provided by  Syariah court  with syariat trial which by the execution done before public.